Heat transfer augmentation of a PTC with rotating absorber, utilizing nanofluid and porous lines. (August 2022) - Aryan, Younes; Jannat Alipour, Mehdi; Siavashi, Majid; Norouzi, Amir Mohammad
Graphical abstract: Highlights: Rotating absorber tube with porous lines and nanofluid tested in a PTC. Rotation caused dramatic 60 K decrease in the max surface temperature of absorber tube. Al2 O3 nanofluid provides higher thermal efficiency, Nu, and surface temperature. 15% & 40% efficiency enhancements met by using porous lines in low- & mid-range Re. Porous lines leads to a 12 K improvement in the outlet temperature. Abstract: Static parabolic trough solar collectors (PTCs) suffer from the localized high surface temperature caused by the focused solar irradiation. Accordingly, the absorber tube of the PTC is assumed to be rotated around its axis via a certain rotational velocity. In the present paper, various nanoparticles such as Al 2 O 3, C u O, and ZnO are studied and compared with each other; also, porous aluminum metal foam lines with three different Darcy numbers of 0.1, 0.01, and 0.001 are utilized. Via the assumption of having a laminar and steady-state flow, a 3D solution is presented. Parameters, including the effect of flow rate, different nanofluids, rotation, and the presence of porous lines on the thermal performance of a solar collector, have been investigated numerically. Results indicate that the utilization of porous lines inside a rotating absorber tube can be resulted in about 15% and 40% in low and mid-range Reynolds improvement in the nanofluid's thermal efficiency compared to the case of not using porous media. Besides, a remarkable 12 K enhancement is reported in the outlet temperature of the nanofluid once porous lines are used. In addition, it is shown that depending on the Darcy number and rotation frequency, the thermal efficiency of the PTC can be increased at least 2%, too.